Field evaluation of feed-based recombinant protein adjuvanted vaccine against streptococcosis in red hybrid tilapia (Oreochromis sp.) - Abu Nor, Nadirah (2015)
Streptococcosis is a fish diseases that are reported in aquaculture systems and can occur in both marine and freshwater fish. This disease is an important bacterial disease in tilapia in many countries including Malaysia. High mass mortalities of Red hybrid tilapia (Oreochromis sp.) have been associated with S. agalactiae, frequently recorded between April and July which depicts the dry season, where the bacterium was isolated from infected Red hybrid tilapia in cage-culturing system in Malaysia. Oral vaccination is a good technique since it required no handling fish, not stressful method, does not require extensive labour, less time consuming and it is may be very effective in fish industry. There is paucity of information on the efficacy of the feed-based recombinant protein- adjuvant vaccine (FRAV) against streptococcosis in tilapia with special regard to humoral and mucosal antibody responses. Therefore, this study was to evaluate the efficacy of the said vaccine, utilizing serum IgM antibody, mucus IgM antibody and gut lavage IgM antibody responses as well as development of gut-associated lymphoid tissue (GALT) in Red hybrid tilapia (Oreochromis sp.) in Kenyir Lake, Hulu Terengganu, Terengganu, Malaysia. This study also conducted to determine the oxidative stress level and mortality in tilapia under heat stress. A commercial Red hybrid tilapia was experimented with S. agalactiae infection under influences of heat stress using plasma malondialdehyde (MDA) and erythrocyte superoxide dismutase (SOD) as biomarkers of stress. To achieve these objectives, 110 fish in good health were divided into five groups of 22 fish in each group. Group A was challenged with 2.3  109 CFU of S. agalactiae and heat stress at 33 ± 0.5C on day 1. Group B was challenged on day 1 as in Group A but heat stress was introduced on day 7 post challenge (pc). Group C was exposed to heat on day 1 and challenged on day 7 pc while group D was challenged on day 1 with no heat stress apply and served as a positive control group. Group E was neither introduced to heat nor challenged (negative control group). Blood samples were collected at day 0, 3, 7, 10 and 14 for MDA and SOD analysis. Overall, Group A, Group B, Group C and Group D showed pattern of increment in MDA analysis as early as on day 3 and decrement pattern for SOD analysis. Group E did not show any significant difference in MDA activities throughout the study period. Besides, study of the immune response of tilapia vaccinated against Streptococcus. agalactiae using a FRAV in a field trial both in rainy and dry seasons was evaluated and mucosal immunity specifically gut-associated lymphoid tissue (GALT) of tilapia was assessed too. To achieve these objectives, 4000 of Red hybrid tilapia were divided into two groups with duplicate. Before the start of experiment, 100 fish was screening by sacrificed them for bacterial isolation. Group 1 and Group 2 were vaccinated group and Group 3 and Group 4 were served as control groups. At month 1, all fish from vaccinated groups were fed with FRAV thrice on day 1. Fish in the control unvaccinated groups were fed with a standard commercial pellet. Booster dose was performed in month 2 of post-vaccination (pv). Fifty fish from each group were sacrificed monthly for sampling by taking their serum, body mucus and gut-lavage fluids to evaluate for antibody responses using indirect ELISA, gut for identification the development of GALT and bacterial isolation for bacteria identification. The result of ELISA showed significant increment (P < 0.05) of all types of antibodies in vaccinated groups when compared to the control groups throughout the study. According to the analyses, exposure to the FRAV was sufficiently to stimulate the aggregation of lymphocytes and development of GALT in vaccinated groups while for control groups; Group 3 and Group 4 only normal scattered of lymphocytes were observed. Bacterial isolation was also performed from the captured fish, which brain, eyes and kidney are used for isolation of S. agalactiae. None of the groups studied, shows the presence of S. agalactiae. In conclusion, this study proved that this FRAV can confer possible protection against streptococcosis to the Red hybrid tilapia either in dry or rainy seasons in Malaysia. Vaccination using FRAV also can stimulate both mucosal and systemic immunities. Therefore, FRAV is the best alternative choice of candidate for the control of streptococcosis in Red hybrid tilapia particularly in Malaysia.